1969
DOI: 10.1038/icb.1969.21
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Actions of 1,10‐phenanthroline and 2,2′‐bipyridine Hydrochlorides, Quaternary Salts and Metal Chelates and Related Compounds

Abstract: Summary. The bacteriostatic activities of stable, inert, coordinately-satnratetl Rn(II) tholates of .suhstitiite;] l.in-phenanthrolin Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 1 publication
5
94
0
Order By: Relevance
“…2). Compared to the antibiotics vancomycin (12) and chloramphenicol (13), all of the copper compounds were more effective in removing biofilms. At 25 µg/mL, chloramphenicol only removed 26% of the biofilm, compared to 60-68% for the compounds 1, 2 and 3, and 35-42% for compounds 7, 8 and 9.…”
Section: Antibiofilm Activity Against S Aureus Mrsa252mentioning
confidence: 99%
See 1 more Smart Citation
“…2). Compared to the antibiotics vancomycin (12) and chloramphenicol (13), all of the copper compounds were more effective in removing biofilms. At 25 µg/mL, chloramphenicol only removed 26% of the biofilm, compared to 60-68% for the compounds 1, 2 and 3, and 35-42% for compounds 7, 8 and 9.…”
Section: Antibiofilm Activity Against S Aureus Mrsa252mentioning
confidence: 99%
“…Early work by the group of Dwyer demonstrated that coordination complexes of Ru(II), Ni(II), Cu(II), Fe(II) or Co(II) with ligands such as 1,10-phenanthroline or 2,2'-bipyridine have activity against both Gram-positive and Gram-negative bacteria [12,13]. As recently reviewed by us, these complexes interact with DNA through intercalation [14].…”
Section: Introductionmentioning
confidence: 99%
“…1,10-Phenanthroline (phen) (Figure 1) and substituted derivatives, both in the metal-free state and as ligands co-ordinated to transition metals, disturb the functioning of a wide variety of biological systems (Butler et al 1969). Furthermore, when the metal-free N,N -chelating bases are found to be bioactive it is usually assumed that the sequestering of trace metals in situ is involved, and that the resulting metal complexes are the active species (MacLeod, 1952;Dwyer et al 1969). Previous work has demonstrated that in RPMI (Roswell Park memorial Institute) medium at 37 • C the metal-based drugs [Cu(phen) 2 (mal)] · 2H 2 O, [Mn(phen) 2 (mal)] · 2H 2 O and [Ag 2 (phen) 3 (mal)] · 2H 2 O (phen = 1,10-phenanthroline; malH 2 = malonic acid) inhibit the growth of C. albicans by around 95% at a concentration of 5 μg/ml Coyle et al 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1969, Dwyer et al [17] reported the bacteriostatic action of metal complexes of 2,2 0 -bipyridyl against selected Gram-positive, Gram-negative and acid-fast bacteria. With the same idea, we have prepared and wish to report some Ruthenium complexes bearing substituted polypyridyl ligands (2,2 0 -bipyridines or 2,2 0 -6 0 ,2 00 -terpyridines) bearing Ru(II)-X moieties where X ¼ Cl, CO, CH 3 CN or H 2 O.…”
Section: Introductionmentioning
confidence: 99%